Activity and expression of histone acetylases and deacetylases in inflammatory phenotypes of asthma. Issue 1 (January 2014) - Gunawardhana, L. P.; Gibson, P. G.; Simpson, J. L.; Powell, H.; Baines, K. J.
Summary Background Histone acetyltransferases (HATs) and histone deacetylases (HDACs) regulate gene expression, yet differences in the activity of these enzymes in the inflammatory phenotypes of asthma are unknown. We hypothesized that neutrophilic asthma (NA) would be associated with increased HAT and decreased HDAC activity. Objective To investigate total HAT/HDAC activity and gene expression in isolated blood monocytes and sputum macrophages from healthy and patients with asthma. Methods Peripheral blood and induced sputum were collected from adults with asthma (n = 52) and healthy controls (n = 9). Sputum inflammatory cell counts were performed and asthma inflammatory phenotypes were classified according to sputum eosinophil and neutrophil cut‐off's of > 3% and > 61% respectively. Peripheral blood monocytes were isolated (n = 61) and sputum macrophages were isolated from a subgroup of patients with asthma (n = 14), using immunomagnetic cell separation. RNA and nuclear proteins were extracted and quantified. Enzyme activity was assessed using fluorescent assays and gene expression of EP300, KAT2B, CREBBP, and HDACs 1, 2 and 3 were measured by qPCR. Results There was a significant inverse association between blood monocyte HAT and HDAC activity (r = −0.58, P < 0.001). NA was associated with increased blood monocyte HAT enzyme activity (P = 0.02), decreased HDAC activity (P = 0.03), and increased HAT: HDAC ratio (P < 0.01) compared with eosinophilic asthma. There were no differences in gene expression of EP300, KAT2B, CREBBP, or HDACs 1, 2 and 3 in blood monocytes from subjects with asthma or inflammatory phenotypes of asthma. There was no effect of inhaled corticosteroid use, poor asthma control, or asthma severity on HAT/HDAC activities. Sputum macrophages had increased expression of KAT2B in eosinophilic compared with paucigranulocytic asthma. Conclusions and Clinical Relevance Neutrophilic airway inflammation is associated with increased HAT and reduced HDAC activity in blood monocytes, demonstrating further systemic manifestations relating to the altered inflammatory gene transcription profile of neutrophilic asthma.